Eksistensi Badan Usaha Milik Nagari (BUMNag) Dalam Mengembangkan Usaha Dan Ekonomi Nagari - Sutri Dahlena; Asdi Agustar; Ira Wahyuni Syarfi (Jurnal Niara, 2023)
The purpose of this study is to obtain facts about the performance of Nagari-Owned Enterprises, to determine the relationship between BUMNag businesses and the economy of the community in each nagari, and to determine the factors that influence the development of BUMNag in West Pasaman Regency. The data collected are primary data and secondary data. The secondary data sources used are from the BUMNag annual report. While the primary data comes from key informants consisting of the Nagari Wali and BUMNag administrators. Data analysis was carried out with descriptive statistics in the form of percentages, averages to describe. The results of the research show that (1) BUMNag has been formally established administratively but not all of them have activities that can become the economic institutions of the respective nagari. The type of business that has been carried out is relevant to the economic mode of the nagari community, but its existence has not been seen as significant. (2) After four (4) years of existence, it turns out that the development of turnover, capital and the scope of activities has not seen any significant development. (3) The development of BUMNag is closely related to the management and performance of its management